The Complementary Roles of Nurses and Physical Therapists in Postoperative Recovery - Hukma, Salihah Ali Ahmed; Nahary, Haniin Ahmed Hassan; Hakami, Sarah Mohammed Hussin; Medabsh, Bayan Yosef; Zangoti, Alaa Mousa Ali; Almutairi, Mona Nijr Salem; Aljebali, Hajar Abdullah Ali; Alsaeed, Muna Fahad (Journal of Posthumanism, 2024)
Postoperative recovery is a critical determinant of surgical success, yet it is fraught with risks including pain, infection, venous thromboembolism, and functional decline. Traditional, discipline-specific care models, where nurses and physical therapists (PTs) work in parallel, often result in fragmented care, leading to suboptimal outcomes and system inefficiencies. This paper presents a theoretical, evidence-based exploration of how structured interprofessional collaboration between nurses and PTs can fundamentally enhance postoperative recovery. Through a comprehensive synthesis of existing research, this paper delineates the distinct and overlapping roles of nursing and physical therapy and argues that a synergistic partnership is essential for modern, high-quality postoperative care. Key collaborative strategies are examined in detail, including multimodal pain management, coordinated early ambulation protocols, integrated wound care, and unified patient education and discharge planning. The analysis extends to formal models of teamwork, such as interdisciplinary rounds and integrated care plans, which provide the necessary structure for effective collaboration. Evidence demonstrates that this integrated approach yields significant, measurable benefits: faster recovery times, shorter hospital stays, reduced rates of complications and readmissions, and improved patient satisfaction. The paper concludes that moving beyond siloed practice to a paradigm of interprofessional synergy is not merely beneficial but a strategic imperative for improving patient outcomes and increasing healthcare value. Recommendations for clinical practice, systemic implementation, and future research are provided to guide the transition toward a more integrated and effective model of postoperative care.